2004
DOI: 10.1002/ange.200454230
|View full text |Cite
|
Sign up to set email alerts
|

An Unusually Fast Nucleophilic Aromatic Displacement Reaction: The Gas‐Phase Reaction of Fluoride Ions with Nitrobenzene

Abstract: Schnell reagiert: Der nucleophile Nitrit‐Fluorid‐Austausch an Nitrobenzol in der Gasphase weist eine Geschwindigkeitskonstante nahe dem Stoßlimit auf. Aus dem berechneten Energieprofil lässt sich schließen, dass die Reaktion über einen nicht in der Ebene erfolgenden Angriff verläuft, wobei der gezeigte Meisenheimer‐Komplex der lokale Übergangszustand der Reaktion ist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 25 publications
3
28
1
2
Order By: Relevance
“…Since that time gas-phase ion-molecule reactions involving aromatic nitrocompounds were not investigated until the beginning of the 21st century when such studies were started in the laboratories of R. Graham Cooks and ours (wide infra). Also, Riveros and coworkers published a short communication in which they described quite unusual gas-phase substitution of the nitro group in nitrobenzene with fluoride anion [12]. It should also be mentioned that in their paper, Riveros et al finally corrected the PA value of the nitrophenide anion, which they found to be equal to 374 Ϯ 3 kcal/mol, about 16 kcal/mol higher than the value measured by Meot-ner and Kafafi in 1988 [13].…”
mentioning
confidence: 92%
“…Since that time gas-phase ion-molecule reactions involving aromatic nitrocompounds were not investigated until the beginning of the 21st century when such studies were started in the laboratories of R. Graham Cooks and ours (wide infra). Also, Riveros and coworkers published a short communication in which they described quite unusual gas-phase substitution of the nitro group in nitrobenzene with fluoride anion [12]. It should also be mentioned that in their paper, Riveros et al finally corrected the PA value of the nitrophenide anion, which they found to be equal to 374 Ϯ 3 kcal/mol, about 16 kcal/mol higher than the value measured by Meot-ner and Kafafi in 1988 [13].…”
mentioning
confidence: 92%
“…A comparison with the gas-phase experimental data shows that the DFT calculations correctly reproduce the experimentally determined thermodynamic enthalpy for the fluorodenitration of nitrobenzene; [25] thus, we deemed the basis set and method to be sufficient for the study of substituted nitrobenzenes. The gas-phase DG8 and DH8 values are large and negative for all fluorodenitration reactions of substituted nitrobenzenes, and an excellent linear freeenergy relationship is produced.…”
mentioning
confidence: 87%
“…[25] The reason for the attenuated solution-phase reactivity is that fluoride, the most densely charged monoanion, is tightly ion paired and Zuschriften strongly solvated. [15,26] Thus, we conducted computational studies to explore the impact of solvent upon the potentialenergy surfaces of fluorodenitration reactions that feature a variety of 4-substituted nitrobenzenes (Scheme 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transition states [18] and stable intermediates [19] of anionic σ-adducts have been reported in gas phase reactions. To understand the reactivity of the prototypical S N Ar reaction, Fernández et al [20] conducted a theoretical investigation of the stability of these structures relative to intrinsic nucleophilicity.…”
Section: Introductionmentioning
confidence: 99%